Gender Differences in Hotel Choice: A Case of Malaysian Muslims - Rosli, Nadzirah; Ha, Norbani Che; Ghazali, Ezlika Mohd; Jano, Zanariah (International Journal of Engineering and Technology, 2018)
The purpose of this study was to provide gendered insights into tourist perceptions in hotel choice among Malaysian Muslims. Specifically, this study was to examine potential gender differences relating to the perceived importance of hotel attributes in building emotional bond with the hotel and post-consumption outcomes. A survey using self-administered questionnaire was conducted and a total of 474 completed and usable questionnaire were utilised for further analysis. A partial-least squares â€“ structural equation modelling was utilised for the data analysis. The findings indicated that there were significant differences between males and females in regards to the effect of hotel attributes on revisit intention and word-of-mouth. Moreover, there was significant difference on the effect of brand attachment on word-of-mouth. The study attempts to fill the gaps in literature that assumes the effects of hotels attributes in building attachment and post-consumption outcomes (i.e., satisfaction, revisit intention and word-of-mouth) are significantly different between males and females.Â  The findings of this study will provide some guidelines and valuable information to stakeholders of hospitality industry in their implementation of marketing strategies.